Influence of Family Support on Patient Quality of Life: Case Study of Hemodialysis Unit at EMC Pulomas Hospital - Deviyana, Evi; Paturohman, Asep; Setyaputri, Pandu Dewi (Journal of Health Science and Medical Therapy, 2025)
Chronic kidney failure is one of the main health problems in the world. Hemodialysis is a treatment method for patients with end-stage chronic renal failure. Patients undergoing hemodialysis perceive their quality of life to be at a low level with their physical condition feeling tired, in pain, and frequently and frequently restless. Family support has a big influence on the health of hemodialysis patients. This study aims to determine the relationship between family support and the quality of life of hemodialysis patients. This type of research uses a descriptive design, with a sampling method, namely a total sampling of 36 respondents and using the chisquare test. The results of the study showed no relationship between family support and the quality of life of patients in the hemodialysis unit at EMC Pulomas Hospital with p-value = 0.0609. Family advice always provides support to respondents in any case and situation.